3D Blind Mesh Quality Assessment Index - Nouri, Anass; Charrier, Christophe; Lézoray, Olivier (Electronic Imaging, 2017)
After the sound, 2D images and videos, 3D models represented by polygonal meshes are the actual emergent content due to the technological advance in terms of 3D acquisition [1]. 3D meshes can be subject to several degradations due to acquisition, compression, pre-treatment or transmission that distort the 3D mesh and therefore affect its visual rendering. Because the human observer is generally located at the end of this line, quality assessment of the content is required. We propose in this paper a viewindependent 3D Blind Mesh Quality Assessment Index (BMQI) based on the estimation of visual saliency and roughness. Given a 3D distorted mesh, the metric can assess the percived visual quality without the need of the reference content as humans do. No assumption on the degradation to evaluate is required for this metric, which makes it powerful and usable in any context requiring quality assessment of 3D meshes. Obtained results in terms of correlation with subjective human scores of quality are important and highly competitive with existing full-reference quality assessment metrics.